2012
DOI: 10.1007/s10615-012-0381-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Social Work Practice with Former System Youth with Mental Health Needs: Perspective of Those in Need

Abstract: The purpose of this study is to describe the types of programs and mental health services former system youth with mental health histories would be inclined to engage in to manage their mental health difficulties, along with the factors that might hinder them from engaging in these services. A series of closed and open-ended questions on potential programs and services were asked, as part of a larger study. Participants were former system youth; specifically 18-30 year olds who were diagnosed with a mood disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Based on previous research, our hypothesis is that the intervention will have the greatest impact if a licensed clinician delivers it collaboratively with a person with lived experience of mental illness and service use. Research shows that young adults with serious mental illnesses want to learn with others who have similar experiences, those who have "been there" [49]. Communication theory supports this view [18,50].…”
Section: Co-facilitation and Collaboration: Licensed Clinician And Pementioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous research, our hypothesis is that the intervention will have the greatest impact if a licensed clinician delivers it collaboratively with a person with lived experience of mental illness and service use. Research shows that young adults with serious mental illnesses want to learn with others who have similar experiences, those who have "been there" [49]. Communication theory supports this view [18,50].…”
Section: Co-facilitation and Collaboration: Licensed Clinician And Pementioning
confidence: 99%
“…Just Do You uses expressive vehicles because young adults report interest in having mental health conversations through creative expression [49]. Further, Malchiodi argues "all expressive therapies focus on encouraging clients to become active participants in the therapeutic process" [51].…”
Section: Communication Through Creative Expression: Bringing Art and mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, young adults reported that they would like to hear from others who have been through similar experiences as the ones that they have been through. 19 Recovery role models are conceptualized as a type of peer in that they also live with a SMHC. However, there is an important distinction between recovery role models and peers, namely they focus on modeling aspects of living independently as an adult with a SMHC and educating by sharing lessons on structured topics (i.e., moving toward acceptance) important to their recovery.…”
Section: Clinical Theories Undergirding the Young Adult Engagement Inmentioning
confidence: 99%
“…Such tailored approaches, which were suggested in previous research, may help to capture and maintain young adult's attention, potentially more than the standard manualized versions of psychoeducation content lessons. 19 In addition to normalizing, these techniques hold youth's attention so as to make an impact on cognitive, social, and affective processes that influence intentions and behaviors.…”
Section: Clinical Theories Undergirding the Young Adult Engagement Inmentioning
confidence: 99%